Case Report: Novel SLC9A6 Splicing Variant in a Chinese Boy With Christianson Syndrome With Electrical Status Epilepticus During Sleep - Liu, Xiaorui; Xie, Lingling; Fang, Zhixu; Jiang, Li (Frontiers in Neurology, 2022)
We investigated the existence and potential pathogenicity of a SLC9A6 splicing variant in a Chinese boy with Christianson Syndrome (CS), which was reported for the first time in China. Trio whole-exome sequencing (WES) was performed in the proband and his parents. Multiple computer prediction tools were used to evaluate the pathogenicity of the variant, and reverse transcription-polymerase chain reaction (RT-PCR) analysis and cDNA sequencing were performed to verify the RNA splicing results. The patient presented with characteristic features of CS: global developmental delay, seizures, absent speech, truncal ataxia, microcephaly, ophthalmoplegia, smiling face and hyperkinesis with electrical status epilepticus during sleep (ESES) detected in an electroencephalogram (EEG). A SLC9A6 splicing variant was identified by WES and complete skipping of exon 10 was confirmed by RT-PCR. This resulted in altered gene function and was predicted to be pathogenic. ESES observed early in the disease course is considered to be a significant feature of CS with the SLC9A6 variant. Combined genetic analysis at both the DNA and RNA levels is necessary to confirm the pathogenicity of this variant and its role in the clinical diagnosis of CS.